CRM as a way to increase the efficiency of management in a virtual organization - Skopiński, Piotr; Zaskórski, Piotr (CRM jako sposób wzrostu efektywności w zarządzaniu wirtualną organizacją, 2012)
The paper attempts to identify the systemic aspects of the use of CRM tools to increase the efficiency of management in the distributed processes organization. It presents the requirements and restrictions for the virtualization of access to technical resources, technology and information in the so-called “cloud” as a way to reduce costly IT investment, especially in SME-class organizations
Informatyka Ekonomiczna = Business Informatics, 2012, Nr 3 (25), s. 173-181
Keywords: CRM; management; distributed processes organization; virtualization; integration; zarządzanie; rozproszona organizacja procesowa; wirtualizacja; integracja